The effectiveness of behavioral knowledge sharing and self -efficacy on management accountant productivity: The role of stewardship theory - Frida Fanani Rohma; Nur Anita (Review of Management, Accounting, and Business Studies, 2025)
This research aims to investigate the effectiveness of knowledge-sharing behavior and self-efficacy in enhancingthe productivity of management accountants. Management accountants hold a vital position in organizations asthey are responsible for managing, analyzing, and reporting both financial and non-financial information tosupport strategic decision-making. Therefore, understanding the specific factors that influence their productivityis essential. This study adopts a quantitative research method with a survey approach, involving managementaccountants from various private sector organizations across Indonesia as respondents. The research findingsdemonstrate that knowledge-sharing behavior significantly contributes to improving management accountants’productivity by fostering collaboration, learning, and innovation. Furthermore, self-efficacy emerges as a criticalfactor, functioning as an internal driver that enhances motivation and work performance through stronger selfregulation. This study extends previous research by focusing explicitly on management accountants, whose uniqueresponsibilities and performance dynamics are often overlooked in broader performance studies, thereby offeringvaluable insights into both theory and practice.